Imaging Atherosclerosis by PET, With Emphasis on the Role of FDG and NaF as Potential Biomarkers for This Disorder - Mayer, Michael; Borja, Austin J.; Hancin, Emily C.; Auslander, Thomas; Revheim, Mona-Elisabeth; Moghbel, Mateen C.; Werner, Thomas J.; Alavi, Abass; Rajapakse, Chamith S. (Frontiers in Physiology, 2020)
Molecular imaging has emerged in the past few decades as a novel means to investigate atherosclerosis. From a pathophysiological perspective, atherosclerosis is characterized by microscopic inflammation and microcalcification that precede the characteristic plaque buildup in arterial walls detected by traditional assessment methods, including anatomic imaging modalities. These processes of inflammation and microcalcification are, therefore, prime targets for molecular detection of atherosclerotic disease burden. Imaging with positron emission tomography/computed tomography (PET/CT) using 18F-fluorodeoxyglucose (FDG) and 18F-sodium fluoride (NaF) can noninvasively assess arterial inflammation and microcalcification, respectively. FDG uptake reflects glucose metabolism, which is particularly increased in atherosclerotic plaques retaining macrophages and undergoing hypoxic stress. By contrast, NaF uptake reflects the exchange of hydroxyl groups of hydroxyapatite crystals for fluoride producing fluorapatite, a key biochemical step in calcification of atherosclerotic plaque. Here we review the existing literature on FDG and NaF imaging and their respective values in investigating the progression of atherosclerotic disease. Based on the large volume of data that have been introduced to the literature and discussed in this review, it is clear that PET imaging will have a major role to play in assessing atherosclerosis in the major and coronary arteries. However, it is difficult to draw definitive conclusions on the potential role of FDG in investigating atherosclerosis given the vast number of studies with different designs, image acquisition methods, analyses, and interpretations. Our experience in this domain of research has suggested that NaF may be the tool of choice over FDG in assessing atherosclerosis, especially in the setting of coronary artery disease (CAD). Specifically, global NaF assessment appears to be superior in detecting plaques in tissues with high background FDG activity, such as the coronary arteries.